Acclimation to wind loads and/or contact stimuli? A biomechanical study of peltate leaves of Pilea peperomioides. (10th December 2021) - Langer, Max; Hegge, Elena; Speck, Thomas; Speck, Olga
Abstract: Plants are exposed to various environmental stresses. Leaves immediately respond to mechano-stimulation, such as wind and touch, by bending and twisting or acclimate over a longer time period by thigmomorphogenetic changes of mechanical and geometrical properties. We selected the peltate leaves of Pilea peperomioides for a comparative analysis of mechano-induced effects on morphology, anatomy, and biomechanics of petiole and transition zone. The plants were cultivated for 6 weeks in a phytochamber divided into four treatment groups: control (no stimulus), touch stimulus (brushing every 30 s), wind stimulus (constant air flow of 4.6 m s −1 ), and a combination of touch and wind stimuli. Comparing the four treatment groups, neither the petiole nor the transition zone showed significant thigmomorphogenetic acclimations. However, comparing the petiole and the transition zone, the elastic modulus ( E ), the torsional modulus ( G ), the E / G ratio, and the axial rigidity ( EA ) differed significantly, whereas no significant difference was found for the torsional rigidity ( GK ). The twist-to-bend ratios ( EI / GK ) of all petioles ranged between 4.33 and 5.99, and of all transition zones between 0.67 and 0.78. Based on the twist-to-bend ratios, we hypothesize that bending loads are accommodated by the petiole, while torsional loads are shared between the transition zone and petiole. Abstract : The petiole and transition zone of peltate leaves of Pilea peperomioides show significant differences in geometrical, mechanical, and structural properties, whereas comparatively small changes were found after wind and/or touch stimulation.